AN ANALYSIS OF STUDENTSâ WRITING SKILL IN DESCRIPTIVE TEXT OF THE SECOND YEAR STUDENTS AT SMPN 2 BANGUN PURBA - Atmono, Haryadi Dwi; Rasyidah, Ummi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research reports on an analysis of the studentsâ writing skill in descriptive text ofthe second year students at SMPN 2 Bangun Purba and also to find out the factors affect it. Thisstudy employed a descriptive research as the research design. This study involved a class ofsecond year students as the sample of the research. The data were collected through writing test.Then, the data were analysed based on their writing test score which were categorized into fivelevels of writing skill (Harris, 1969) and two organization structures of descriptive text(Identification and description) as the indicators to see the studentsâ writing skill in descriptivetext. The findings of the study show some points. The first point is that, generally, the studentsâmean score of writing skill particularly in writing descriptive text was 56 and it was consideredas the average level of skill. The second is that there are two factors affect the studentsâ writingskill. They are related to (1) the components of writing (grammar, vocabulary, mechanics, style,organization) and (2) the organization structure of descriptive text (identification anddescription).